Increasing the Potential of Productive Waqf through Cash Waqf as a Model for Local Economic Development - Fahath Haikal Aziz; Mugiyati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In the midst of efforts to build a more inclusive and equitable economic system, cash waqf has emerged as a strategic alternative in encouraging sustainable local economic growth. As an Islamic social financial instrument, cash waqf has high flexibility and great potential in bridging the role of the community in financing development, especially in productive sectors such as MSMEs, education, and health services. This study uses a qualitative approach based on literature studies to examine how the cash waqf management mechanism can be optimized to empower the community economy. The results of the study show that although there is a regulatory framework and initiatives such as the National Cash Waqf Movement (GNWU), its implementation still faces challenges in the form of low community literacy, limited manager capacity (nazhir), and minimal incentives for waqf. However, through accountable governance, utilization of digital technology, and development of waqf investment schemes such as Cash Waqf Linked Sukuk (CWLS), cash waqf has the potential to become a driving force for economic development based on spiritual and social values. This study recommends strengthening waqf institutions, increasing public education, and integrating cash waqf into regional economic policies to create broader and more sustainable social impacts.